Comparative life cycle assessment of polyethylene agricultural mulching film and alternative options including different end-of-life routes. (May 2023) - Tan, Quanyin; Yang, Liyao; Wei, Fan; Chen, Yuan; Li, Jinhui
Abstract: With rising concerns about adverse impacts of agricultural plastic waste in the soil environment and microplastic problems, many options have been proposed to prevent agricultural plastic pollution. To evaluate the options environmentally, this study conducted a comparative life cycle assessment of mulching films with different thicknesses (0.01 mm and 0.014 mm), materials (polyethylene and poly (butylene adipate- co -terephthalate)), and end-of-life options (recycling, incineration and biodegradation). The results indicate that biodegradable film presents the lowest net environmental impacts in aquatic pollution and toxicity indicators, while the 0.014 mm polyethylene film performs the best in global warming potential and fossil resource depletion. Either reducing the soil content or increasing the collection rate of waste polyethylene films can reduce their environmental impacts, and the reducing proportions of 0.014 mm polyethylene films were found to be larger than those of 0.01 mm polyethylene films. In general, the biodegradable mulching film is found to be more environmental-friendly than polyethylene film, but potential improvement could be considered for greener design of the products by increasing biobased material. More efforts can be put on developing reliable inventory datasets of biodegradable materials production. Graphical abstract: Image 1 Highlights: A comparative life cycle assessment is conducted for agricultural mulching films. Littering of PE contributes the most to toxicity and eutrophication categories. Thick PE film performs the best on carbon emission and resource consumption. Biodegradable film performs the best in toxicity impact categories.